2021
DOI: 10.1038/s41467-021-21066-x
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput phenotypic screen and transcriptional analysis identify new compounds and targets for macrophage reprogramming

Abstract: Macrophages are plastic and, in response to different local stimuli, can polarize toward multi-dimensional spectrum of phenotypes, including the pro-inflammatory M1-like and the anti-inflammatory M2-like states. Using a high-throughput phenotypic screen in a library of ~4000 FDA-approved drugs, bioactive compounds and natural products, we find ~300 compounds that potently activate primary human macrophages toward either M1-like or M2-like state, of which ~30 are capable of reprogramming M1-like macrophages tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 60 publications
5
64
0
1
Order By: Relevance
“…Based on this concept, Hu et al identified approximately 30 compounds that can switch M1-like phenotypes toward the M2-like TAMs and that another ~20 compounds can switch M2-like TAMs to the M1 phenotype through high-throughput screening [ 119 ]. Furthermore, they showed that thiostrepton could reprogram TAMs toward an M1-like state in mice and has the anti-tumor ability [ 119 ]. In addition to pharmacological approach, oligonucleotide delivery is also a promising and popular method to manipulate TAMs.…”
Section: Immunotherapy and Tam-targeted Therapymentioning
confidence: 99%
“…Based on this concept, Hu et al identified approximately 30 compounds that can switch M1-like phenotypes toward the M2-like TAMs and that another ~20 compounds can switch M2-like TAMs to the M1 phenotype through high-throughput screening [ 119 ]. Furthermore, they showed that thiostrepton could reprogram TAMs toward an M1-like state in mice and has the anti-tumor ability [ 119 ]. In addition to pharmacological approach, oligonucleotide delivery is also a promising and popular method to manipulate TAMs.…”
Section: Immunotherapy and Tam-targeted Therapymentioning
confidence: 99%
“…Their versatility is attributed to their ability to respond to specific physiological or pathological cues, leading to their polarization into different states, each with a distinct functional phenotype. A range of molecular triggers that cause differentiation in macrophages is known (Hu et al, 2021;Jaguin et al, 2013;Xue et al, 2014). It is also well known that the differentiation spans a full spectrum of phenotypes with the classically activated M1 and the alternatively activated M2 states at two ends of the spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…It is of great interest to identify TFs that are most influential in guiding the polarization. Given the importance of macrophages, several studies have investigated the variations in the transcriptomes in different diseases (Benoit et al, 2008;Mosser and Edwards, 2008;Ross et al, 2021;Schultze, 2016;Zheng et al, 2018) exposure of macrophages to different exogenous and endogenous stimuli (Hu et al, 2021;Jaguin et al, 2013;Xue et al, 2014), which have resulted in a wealth of data that are publicly accessible. These large datasets provide opportunities for addressing a variety of questions.…”
Section: Discussionmentioning
confidence: 99%
“…Reprogramming TAMs could therefore be a more efficacious approach, providing a strategy where pro-tumoral macrophages can be re-educated towards an anti-tumoral phenotype to create a microenvironment that reject rather than nurture tumor cells. There are several strategies currently used to reprogram TAMs to be anti-tumorigenic in preclinical and clinical investigation including toll-like receptor agonists and monoclonal antibodies that induce TAM antitumor effects (260), and Hu et al have recently identified many more (261). Trabectedin is an anti-cancer agent that in addition to directly targeting certain types of cancer cells, it also induces apoptosis in monocytes and macrophages.…”
Section: Targeting Tam Recruitment and Polarizationmentioning
confidence: 99%
“…There are several strategies currently used to reprogram TAMs to be anti-tumorigenic in preclinical and clinical investigation including toll-like receptor agonists and monoclonal antibodies that induce TAM anti-tumor effects ( 260 ), and Hu et al. have recently identified many more ( 261 ). Trabectedin is an anti-cancer agent that in addition to directly targeting certain types of cancer cells, it also induces apoptosis in monocytes and macrophages.…”
Section: Therapeutically Targeting Macrophage and Cancer Crosstalk In Bone Metastasesmentioning
confidence: 99%